RIAU MALAY ETHNOPARENTING ON CHILDREN AGED 4-6 YEARS IN THE BUKIT PAYUNG TRANSMIGRATION AREA IN KAMPAR - Farah Nurhaliza; Ria Novianti; Defni Satria (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This paper discusses the activities that are related to parenting, which is interrelated with a culture in order to be described through the point of view based on the indigenous people. The research uses a qualitative approach with ethnographic methods. Data were collected through an interview process and subsequently were analyzed by using the Nvivo 12.2 Software coding technique. The Malay ethnoparenting based on Tunjuk Ajar Melayu through the